2022
DOI: 10.3390/jcm11206164
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Morphological and Digital-Assisted Analysis for BCL6 Endometrial Expression in Women with Endometriosis

Abstract: BCL6 (B-cell lymphoma 6) is a proto-oncogene and transcriptional repressor initially described as being involved in B-cell lymphoma. Recently, this factor has been identified as a promising tissue biomarker which could be used to diagnose women affected by endometriosis. Previous studies used HSCORE for BCL6 staining quantification in the endometrium. However, this semi-quantitative technique of analysis has some limitations, including a lack of objectivity, robustness, and reproducibility that may lead to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(57 reference statements)
0
0
0
Order By: Relevance
“…Evans-Hoeker et al confirmed BCL6 overexpression in the eutopic endometrium of women with endometriosis [ 9 ]. Squatrito et al compared the endometrial expression of BCL6 between fertile and infertile women with and without endometriosis independently of the stage by using HSCORE analysis [ 10 ]. However, HSCORE analysis is known to be biased in its objectivity and reproducibility.…”
Section: Reviewmentioning
confidence: 99%
“…Evans-Hoeker et al confirmed BCL6 overexpression in the eutopic endometrium of women with endometriosis [ 9 ]. Squatrito et al compared the endometrial expression of BCL6 between fertile and infertile women with and without endometriosis independently of the stage by using HSCORE analysis [ 10 ]. However, HSCORE analysis is known to be biased in its objectivity and reproducibility.…”
Section: Reviewmentioning
confidence: 99%